Second representative of the order Misophrioida (Crustacea, Copepoda) from Australia challenges the hypothesis of the Tethyan origin of some anchialine faunas - Karanovic, Tomislav; Eberhard, Stefan M. (Zootaxa, 2009)
A new species of the genus Speleophria is described from a cave in the Nullarbor region in southern Western Australia. Its congeners include species from the Balearics, Croatia, Bermuda, Yucatan peninsula and north-western Western Australia, all considered to be Tethyan relicts. However, the discovery of the new speleophriid in the Nullarbor region has important biogeographic and ecological implications. From the biogeographic perspective, it either suggests dispersal as the process determining the current distribution pattern of the aquatic fauna found on the Roe Plains or significantly extends the Tethyan track across Australia, from the north-western coastal margin of the continent to the southern coastal margin. From an ecologic perspective, the new speleophriid suggests the possible existence of anchialine habitats in southern Australia. Speleophria nullarborensis sp. nov. can be distinguished from its four congeners by its plesiomorphic 3-segmented endopod of the first swimming leg (2-segmented in other species) and unusually long innermost apical seta on the caudal ramus. Another character that easily distinguishes our new species, and seems to be an autapomorphic feature, is its constricted preanal somite.